High data retrieval rates with SwissPedData for paediatric traumatic brain injuries in children’s hospitals: a multicentre, point-prevalence study - Michael von Rhein; Niklaus Krayenbühl; Andreas Meyer-Heim; Sergio Manzano; Gianluca Gualco; Renato Gualtieri; Fabrizio Romano; Alexander Mack; Larissa Hauser-Angst; Michelle Seiler (Swiss Medical Weekly, 2025)
STUDY AIMS: SwissPedNet aims to improve the quality of multicentre research through standardised documentation of routine healthcare data. Therefore, SwissPedData was developed as a set of defined common data elements to be documented in each electronic patient file in a standardised format. This study evaluates the preparedness of the ten SwissPedNet hospitals for SwissPedData before its nationwide implementation, focusing on: (a) whether the defined common data elements are effectively documented and can be retrieved for children presenting with traumatic brain injuries to paediatric emergency departments, and (b) analysis of the content of these common data elements to assess how children with traumatic brain injuries are treated in paediatric emergency departments across Switzerland.